Associations of complete blood count parameters with pancreatic beta‐cell function and insulin resistance in prediabetes and type 2 diabetes mellitus. Issue 6 (13th May 2022) - Nah, Eun‐Hee; Cho, Seon; Park, Hyeran; Kim, Suyoung; Cho, Han‐Ik
Abstract: Introduction: Previous studies found controversial associations of CBC parameters with pancreatic beta‐cell function (BCF) and insulin resistance (IR). The aim of this was to determine the independent associations of CBC parameters with BCF and IR in prediabetes and type 2 diabetes mellitus (T2DM). Methods: This study selected subjects who underwent health checkups at 16 health‐promotion centers in 13 Korean cities during 2021. The subjects comprised 1470 patients with normoglycemia, 1124 with prediabetes, and 396 with T2DM. BCF and IR were assessed using the homeostasis model assessment (HOMA)‐β and HOMA‐IR, respectively. Correlation and multiple linear regression analyses were used to determine the correlation between CBC parameters and HOMA. Results: While HOMA‐IR gradually increased according to red blood cell count quartiles (1.22, 1.40, 1.47, and 1.91, in the first, second, third, and fourth quartiles, respectively; p < 0.001), there was no correlation after adjusting for waist circumference (WC) and HbA1c. The red blood cell distribution width (RDW) was associated with HOMA‐ β [coefficient ( β ) = 15.527, p = 0.002], but not with HOMA‐IR. White blood cells (WBCs) were associated with HOMA‐IR and HOMA‐β, which was stronger in HOMA‐β ( β = 0.505 vs 15.171, p = 0.002) after adjusting for WC and HbA1c. The platelet count was correlated with HOMA‐IR and HOMA‐β, which only remained in HOMA‐β ( β = 15.581, p = 0.002) after adjusting for WC and HbA1c. Conclusion: RDW, WBC, and platelet counts were independently associated with only HOMA‐β in prediabetes and T2DM. This suggests that these CBC parameters could represent BCF in prediabetes and T2DM. Abstract : The aim of this was to determine the independent associations of complete blood cell (CBC) parameters with beta‐cell function (BCF) and insulin resistance (IR) in prediabetes and type 2 diabetes mellitus (T2DM). Correlation and multiple linear regression analyses were used to determine the correlation between CBC parameters and the homeostasis model assessment (HOMA). The red blood cell distribution width (RDW), White blood cells (WBCs) and platelet counts were independently associated with only HOMA‐β in prediabetes and T2DM after adjusting for waist circumference and HbA1c. This suggests that these CBC parameters could represent BCF in prediabetes and T2DM.